presidential decree-law no. 55/2014 on amending some provisions of the mortgage law and law promulgating it no.148/2001 - Egypt (2025)
Decree-Law of the President of the Arab Republic of Egypt No. 55 of the Year 2014 on amending some provisions of the mortgage law and the law promulgating it no. 148 of the year 2001 – قرارا رئيس جمهورية مصر العربية بالقانون رقم 55 لسنة 2014 بتعديل بعض أحكام قانون التمويل العقارى والقانون الصاتدر به رقم 148 لسنة 2001